Japan's Security Relations with China since 1989 - Drifte, Reinhard (Taylor & Francis, 2025)
Japan's Security Relations with China since 1989 raises the crucial question of whether Japan's political leadership which is still preoccupied with finding a new political constellation and with overcoming a deep economic crisis is able to handle such a complex policy in the face of an increasingly assertive China and a US alliance partner with strong swings between engaging and containing China's power. This study of the highly topical bilateral relationship will be of great interest to students and researchers in Japanese and Chinese Studies, Politics, International Relations and Security Studies.